1980
DOI: 10.1007/bf00440617
|View full text |Cite
|
Sign up to set email alerts
|

Influence de la concentration du glucose et de l'azote sur la morphologie de Candida albicans et la formation de ses chlamydospores dans un milieu de culture synth�tique

Abstract: Candida albicans was grown in the darkness, at 28 degrees C, in a synthetic medium in which glucose and nitrogen concentrations were varied. Numeric appraisal of the chlamydospore index was possible only in the medium where glucose concentration was 0,08 g/1 or less. When the glucose concentration raised, pseudomycelial thalli bore numerous chlamydospores but sometimes also chains of cells with a dense granular content. These thalli bud yeast cells which separate and bud again in the medium. The different morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…When grown in the presence of glucose at low pH values, the budding cells, also, apparently did not separate, which resulted in the formation of large clusters of multiple-budded cells or pseudohyphae. Similar modes of growth have been reported previously in response to glucose at lower temperatures (Soll & Bedell, 1978;Dujardin et al, 1980). It might be useful to use this phenomenon to distinguish between growing and non-growing cells at low pH or low temperatures.…”
Section: Discussionsupporting
confidence: 75%
“…When grown in the presence of glucose at low pH values, the budding cells, also, apparently did not separate, which resulted in the formation of large clusters of multiple-budded cells or pseudohyphae. Similar modes of growth have been reported previously in response to glucose at lower temperatures (Soll & Bedell, 1978;Dujardin et al, 1980). It might be useful to use this phenomenon to distinguish between growing and non-growing cells at low pH or low temperatures.…”
Section: Discussionsupporting
confidence: 75%
“…Chlamydospore formation is especially abundant on solid media under glass coverslips providing microaerophilic conditions (Dalmau inoculation technique). The presence of glucose inhibits chlamydospore formation, while nitrogen levels have no major influence (5). Light inhibits chlamydospore formation (6).…”
mentioning
confidence: 99%
“…Morphological transitions that are triggered by nitrogen starvation include pseudohyphal growth of diploid S. cerevisiae (Gimeno et al, 1992) and the Gcn4-dependent filamentation by C. albicans (Tripathi et al, 2002). Some impact of nitrogen on chlamydosporulation has also been described for C. albicans (Jansons and Nickerson, 1970b; Dujardin et al, 1980b) but no such information is available for C. dubliniensis so far. Hence, we tested the effect of nutrient addition to chlamydospore-inducing corn meal tween (CM) agar and rice agar.…”
Section: Resultsmentioning
confidence: 99%
“…However, in Candida the term chlamydospore does not refer to a functional, but rather to a morphological unit: Although Candida chlamydospores resemble such spores and are high in lipid droplets for energy supply (Jansons and Nickerson, 1970a), they are not more resistant to heat, starvation, or dryness compared to yeast cells (Citiulo et al, 2009). Nevertheless, early studies reported a correlation between nutrient supply and induction of chlamydospore formation of the fungus (Jansons and Nickerson, 1970b) where glucose, in contrast to nitrogen, had a strong repressive effect (Dujardin et al, 1980b). Typical inducing media on the other hand are rich in complex carbon sources (e.g., corn or rice meal) and frequently contain detergents.…”
Section: Introductionmentioning
confidence: 99%